Female leadership: a qualitative study - Taveira, Marta Pinho; Silva, Susana (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
Several studies have shown that women have the same levels and sometimes higher levels of training than men and account for about 50% of the workforce. Yet women are underrepresented in higher hierarchical positions. The number of women in positions of high power and authority has increased, altough there are obstacles to female advancement to the highest levels of the organizational hierarchy (Catalyst, 2017a; Catalyst, 2017b; Eurostat 2016; Grant Thornton, 2016). Factors, such as cultural and social norms, as well as women's roles and responsibilities, may result in biased perceptions of women and their ability to lead (Haile, Emmanuel & Dzathor, 2016) appearing as some of the barriers that justify the lesser female presence in top positions. The barriers identified by Diehl and Dzubinski (2016), operate on several levels. Difficulties are identified at the level of society in general, at the organizational level and finally at the individual level. Some metaphors are used to illustrate the difficulties faced by women in the context of work, namely the labyrinth, wich symbolizes the difficulties women face troughout their career; the sticky floor, that represents the challenges women face at an early fase of their carrer; or the glass ceiling, representing the fact that women are unable to advance to the highest levels of leadership and are retained at the last level. Women can only advance to the highest level of leadership by breaking this invisible "ceiling" (Carli & Eagly, 2016). Therefore, the aim of this study is to characterize female leadership, more specifically to explore the obstacles and opportunities. In this qualitative study, were used semi-structured interviews to collect data. The participants were ten women in leadership positions, with an averege age of 40 years old and they were in leadership positions for nine years in avarege. Data was analyzed according to thematic analysis procedures (Braun & Clarke, 2006). The results of this study suggest that female leadership is characterized by some challenges, mainly gender bias and difficulties at personal, family and professional level, but it is mainly characterized by opportunities. Gender bias represents a challenge that operates at the social and organizational level, on the one hand, women are given family responsibilities that originates higher workload (Haile et al., 2016), on the other hand, some of the stereotypes and prejudices existing outside the organizations are later transported to the organizational environment, which results in a devaluation and limitation of female leadership (Diehl & Dzubinski, 2016). Stress (Grandey & Cropanzano, 1999) the high workload with family and home (Torres et al., 2018) and the difficulty in finding role models and women's mentors also represent some of the challenges found (Diehl & Dzubinskil, 2016). Opportunities arise through the support that the leaders receive (Cheung & Halpern, 2010), through the combination of some personal characteristics and also through the use of strategies that allow reconciliation of personal and professional life (Allen, Johnson, Kiburz & Shockley, 2013). Developmental practices, such as mentoring (Allen, Eby, Poteet, Lentz & Lima, 2004) and coaching (Day, 2000), are also conductive to female leadership. Finally, some opportunities were identified in the context of personal, family and professional life, such as the importance of moments to rest and self-care (Grandey & Cropanzano, 1999), time with family (Kossek, 2016) and also the importance of making a strategic career management and decision making (Kossek, Roberts, Fisher & DeMarr, 1998; Hopkins, O’Neil, Passarelli & Bilimoria, 2008). It is possible to conclude that, although the executive world is still very masculine, the presence of women in top leadership positions is increasing. Even though this process is slow and gradual, women are positioning themselves to achieve even greater success in the future. References Allen, T. D., Eby, L. T., Poteet, M. L., Lentz, E., & Lima, L. (2004). Career Benefits Associated With Mentoring for Proteges: A Meta-Analysis. Journal Of Applied Psychology, 89(1), 127-136. doi:10.1037/0021-9010.89.1.127. Allen, T. D., Johnson, R. C., Kiburz, K. M., & Shockley, K. M. (2013). Work-Family Conflict and Flexible Work Arrangements: Deconstructing Flexibility. Personnel Psychology, 66(2), 345-376. doi:10.1111/peps.12012. Braun, V., & Clarke, V. (2006). Using thematic analysis in psychology. Qualitative Research In Psychology, 3(2), 77-101. doi:10.1191/1478088706qp063oa. Carli, L. L., & Eagly, A. H. (2016). Women face a labyrinth: an examination of metaphors for women leaders. Gender In Management, 31(8). doi:10.1108/GM-02-2015-0007. Catalyst (2017a). S&P 500 Pyramids: Methodology. Nova Iorque: Catalyst, August 22nd, 2017. Accessed on December 12th 2017 in http://www.catalyst.org/system/files/sp_500_pyramids_methodology_final_082817.pdf Catalyst (2017b) Quick Take: Women on Corporate Boards Globally. New York: Catalyst, January 4th, 2017. Accessed a on december 12th 2017 in http://www.catalyst.org/knowledge/women-corporate-boards-globally Cheung, F. M., & Halpern, D. F. (2010). Women at the top: powerful leaders define success as work + family in a culture of gender. The American Psychologist, 65(3), 182-193. doi: 10.1037/a0017309. Day, D. V. (2000). Leadership Development: A review in context. Leadership Quarterly, 11(4), 581-613. doi:10.1016/S1048-9843(00)00061-8. Diehl, A. B., & Dzubinski, L. M. (2016). Making the Invisible Visible: A Cross-Sector Analysis of Gender-Based Leadership Barriers. Human Resource Development Quarterly, 27(2), 181-206. doi:10.1002/hrdq.21248. Eurostat (2016). Eurostat regional yearbook. Comissão Europeia. doi: 10.2785/29084 Accessed on December 12th 2017 in http://ec.europa.eu/eurostat/documents/3217494/7604195/KS-HA-16-001-EN-N.pdf Grandey, A. A., & Cropanzano, R. (1999). Regular Article: The Conservation of Resources Model Applied to Work–Family Conflict and Strain. Journal Of Vocational Behavior, 54, 350-370. doi:10.1006/jvbe.1998.1666. Grant Thornton International Ltd. (2016). Women in business: Turning promise into practice. Accessed on December 12th 2017 in https://www.grantthornton.global/globalassets/wib_turning_promise_into_practice.pdf Haile, S., Emmanuel, T., & Dzathor, A. (2016). Barriers and challenges confronting women for leadership and management positions: review and analysis. International Journal Of Business And Public Administration, 13(1), 36-51. Hopkins, M. M., O’Neil, D. A., Passarelli, A., & Bilimoria, D. (2008). Women’s leadership development strategic practices for women and organizations. Consulting Psychology Journal: Practice and Research, 60(4), 348-365. doi: 10.1037/a0014093. Kossek, E. E. (2016). Managing work-life boundaries in the digital age. Organizational Dynamics, 45, 258-270. doi:10.1016/j.orgdyn.2016.07.010. Kossek, E. E., Roberts, K., Fisher, S., & DeMarr, B. (1998). Career self-management: a quasi-experimental assessment of the effects of a training intervention. Personnel Psychology, 51(4), 935-962. doi: 10.1111/j.1744-6570.1998.tb00746.x.